Bond Rating Methods: Comparison and Validation - Ang, James S.; Patel, Kiritkumar A. (Journal of Finance, 1975)
James S. Ang, Kiritkumar A. Patel, Bond Rating Methods: Comparison and Validation, The Journal of Finance, Vol. 30, No. 2, Papers and Proceedings of the Thirty-Third Annual Meeting of the American Finance Association, San Francisco, California, December 28-30, 1974 (May, 1975), pp. 631-640